2019
DOI: 10.1111/1750-3841.14427
|View full text |Cite
|
Sign up to set email alerts
|

Development of Protein‐Based High‐Oxygen Barrier Films Using an Industrial Manufacturing Facility

Abstract: In this study, protein-based high-oxygen barrier multilayer films were manufactured at a pilot plant scale by a roll-to-roll coating process and an adhesive lamination process. Also, their characteristics were examined to evaluate their industrial feasibility. Oxygen transmission rates (OTRs) of the protein-based films (polyethylene terephthalate [PET]/pea protein isolate [PPI]/nylon/cast polypropylene [CPP], PET/whey protein isolate [WPI]/CPP, PET/WPI/nylon/CPP, and PET/PPI/nylon/low-density polyethylene [LDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
8
1
1
Order By: Relevance
“…This leads to the protein film varying in structure based on the source of protein, providing different oxygen permeabilities. Films that are composed of plant protein isolates have excellent oxygen barrier properties due to their polar nature and crosslinked polymer network; however, the water vapor barrier is low [ 16 , 22 ]. Chang et al showed that whey or pea protein isolate film coatings have lower oxygen permeability compared to multilayers containing nylon as the oxygen barrier: The multilayer PET/WPI/cast polypropylene package has 90 times lower oxygen permeability compared to the PET/nylon/cast polypropylene control multilayer.…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to the protein film varying in structure based on the source of protein, providing different oxygen permeabilities. Films that are composed of plant protein isolates have excellent oxygen barrier properties due to their polar nature and crosslinked polymer network; however, the water vapor barrier is low [ 16 , 22 ]. Chang et al showed that whey or pea protein isolate film coatings have lower oxygen permeability compared to multilayers containing nylon as the oxygen barrier: The multilayer PET/WPI/cast polypropylene package has 90 times lower oxygen permeability compared to the PET/nylon/cast polypropylene control multilayer.…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
“…Chang et al showed that whey or pea protein isolate film coatings have lower oxygen permeability compared to multilayers containing nylon as the oxygen barrier: The multilayer PET/WPI/cast polypropylene package has 90 times lower oxygen permeability compared to the PET/nylon/cast polypropylene control multilayer. The PET/pea protein isolate/nylon/cast polypropylene CPP multilayer showed nearly 1000 times better oxygen permeability [ 22 ].…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the polymer strands are banded together by relatively weak intermolecular attractions, which need much less strength to break than MD film (Phua, Chow, & Mohd Ishak, 2011). Several previous researchers (Battisti et al, 2017;Chang et al, 2019;Sun, Lu, Qiu, & Tang, 2017) have also documented the lower mechanical strength of the TD in the developed film than the strength of the MD.…”
Section: Resultsmentioning
confidence: 99%
“…CD treatment can increase polymer surface energy by surface oxidation and formation of polar functional groups including phenolic hydroxyl, carbonyl, and carboxyl (O'Hare et al, 2002). The organic and inorganic materials, such as cast polypropylene (Chang et al, 2019), linear low-density polyethylene (LDPE), nylon (Joo et al, 2018), phosphate glass (Lin, Tyler, Sun, Shi, & Schiraldi, 2017), SiO x (Wang et al, 2014), SiO x N y (Yonekura, Fujikawa, & Murakami, 2010), and AlO x (Struller, Kelly, & Copeland, 2014), coated on plastic materials have been reported. However, there is no study concerning the combination of WPI/CS/MCCbased coating and surface pretreatment including CD and UGD to improve the barrier properties of PET.…”
mentioning
confidence: 99%